Case Report: Glucocorticoids Combined With Immunosuppressant in the Treatment of Acromegaly Complicated With Focal Segmental Glomerulosclerosis - Wang, Ruiqiang; Wu, Yunqi; An, Dongyue; Ma, Pupu; Guo, Yuanyuan; Tang, Lin (Frontiers in Medicine, 2021)
Background: Acromegaly is a chronic disease caused by excessive secretion of growth hormone (GH), which circulates and stimulates the liver and body tissues to produce insulin-like growth factor type 1 (IGF-1). Experimental studies have shown that excessive secretion of GH is related to glomerular sclerosis, and elevated IGF-1 levels may be involved in the occurrence of glomerular hypertrophy. But relevant clinical cases are rare. Here, we reported a case of acromegaly complicated with focal segmental glomerulosclerosis (FSGS). Case Presentation: A 49-year-old man was admitted to our hospital because of acromegaly for more than 10 years and proteinuria for more than 3 years. Acromegaly was confirmed by contrast-enhanced magnetic resonance imaging, minimally invasive surgery and pathology. The results of renal biopsy showed FSGS-NOS (not otherwise specified) with ischemic renal injury and mesangial IgA deposition. One month after transnasal transsphenoidal space occupying resection, GH and urinary protein decreased significantly, and nephropathy was partially relieved. In the next 4 months, GH stabilized at the normal level, while urinary protein gradually increased. When the urinary protein increased to 4.2 g/d, the dosage of glucocorticoids increased to 20 mg/d, and tacrolimus 1 mg/d were added, and the urinary protein decreased again. However, when the urinary protein decreased to 0.43 g/d, the patient stopped taking glucocorticoids and tacrolimus, and the urinary protein increased to 2.85 g/d after 8 months, but the GH was still in the normal range. Conclusion: In this case, GH is partially involved in the formation of FSGS. Not only does surgery reduce the effects of GH, but low doses of glucocorticoids and immunosuppressant are effective in slowing the progression of kidney disease, at least in reducing urinary protein.